Reconfiguration of Distribution Networks with Presence of DGs to improving the Reliability - Amir Sabbagh Alvani; Seyed Mehdi Mahaei (Institute of Advanced Engineering and Science, 2016)
In this paper, the network reconfiguration in the presence of distributed generation units with the aim of improving the reliability of the network is studied. For this purpose four reliability parameters in the objective function are considered, which is average energy not supplied system average interruption frequency index, system average interruption duration index and momentary average interruption frequency index. The new method will be normalized objective function. Another suggestion of this paper are considering the different fault rates, locating time of faults type and prioritization of customers based on their importance. This nonlinear problem has optimized by particle swarm optimization (PSO) algorithm.